HIGH-ORDER MOMENTS OF THE SUM OF RANDOM VARIABLES USING THE METHOD OF CHARACTERISTIC FUNCTIONS - Dushatov N. T. (Web of Journals Publishing, 2025)
The problem of determining the order moment of the sum of random variables (r.v.) using the method of characteristic functions (ch.f.) is studied in the article. order moment of the sum of independent and dependent r.v.-es subject to the exponential law with the parameter is found.
Keywords: Random variable, density function, exponential distribution, characteristic function, order moment, correlation coefficient, numerical covariance coefficient, conjugate density function.